MENGEKSPLORASI STRATEGI MANAJEMEN KELAS BAHASA INGGRIS DI SEKOLAH DASAR INKLUSI - Cicih Wiarsih; Feisal Aziez (Khazanah Pendidikan, 2021)
This research aims at: (1) exploring classroom management strategies used by English teachers in inclusive elementary school in Banyumas regency, (2) exploring English teachers’ reasons in using the strategies in their inclusive classes, (3) exploring how English teachers accommodate various needs of students with special needs in the classroom. This is a descriptive qualitative research. The primary data was gathered through classroom observation while secondary data was collected through interviews. This research was done in two inclusive elementary schools in Banyumas regency. This study shows that English teachers in the school have good understanding on classroom management. However, the practice in the classroom indicates that there are still rooms for improvement.